Pembinaan Santri untuk Menumbuhkan Jiwa Leadership Islam di Pondok Pesantren Modern Bantul Yogyakarta - Hodiri Adi Putra; Nor Wijayanti; Sri Yuni Tursilowati; Sri Sularsih Endartiwi; Woro Ispandiyah; Julaikah Julaikah; Amyati Amyati (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
Islamic boarding school-based leadership requires someone who has Islamic boarding school-style leadership criteria, such as adaptive, selective, independent, strong and adhering to Islamic teachings in order to create an ideal education system. The purpose of this service is to explain the basics and foundations of Islamic leadership in the Qur'an and Hadith to students and Islamic boarding school administrators who are carrying out their duties in applying the knowledge they have gained at the Islamic boarding school to be put into practice at the Islamic boarding school. This community service method takes the form of coaching activities for students regarding Islamic leadership which is carried out offline. The number of students who took part in this service activity was 73 students. The results of the service activities showed that the students were enthusiastic about participating in this activity and were able to understand Islamic leadership such as self-management and practicing discipline in participating in activities at the Islamic boarding school and not using things that were not their rights. The benefit of this service activity is that the students can apply and understand Islamic leadership both while inside the Islamic boarding school and outside the Islamic boarding school.